1994
DOI: 10.1038/ng0994-98
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the fibroblast growth factor receptor 2 gene cause Crouzon syndrome

Abstract: Crouzon syndrome is an autosomal dominant condition causing premature fusion of the cranial sutures (craniosynostosis) and maps to chromosome 10q25-q26. We now present evidence that mutations in the fibroblast growth factor receptor 2 gene (FGFR2) cause Crouzon syndrome. We found SSCP variations in the B exon of FGFR2 in nine unrelated affected individuals as well as complete cosegregation between SSCP variation and disease in three unrelated multigenerational families. In four sporadic cases, the normal paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
325
0
11

Year Published

1995
1995
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 698 publications
(341 citation statements)
references
References 32 publications
5
325
0
11
Order By: Relevance
“…We have identified bone as the principle target tissue for the physiological effects of FGF-2 overexpression during growth and development. This phenotype is consistent with in vitro data showing changes in the growth and differentiation of chondrocytes by addition of exogenous FGF-2 (Trippel et al, 1993) and human syndromes where mutation of FGFR tyrosine kinases primarily affect the skeletal system (Jabs et al, 1994;Muenke et al, 1994;Reardon et al, 1994;Rousseau et al, 1994;Shiang et al, 1994;Tavormina et al, 1995). The Western blots and RNase protection assays suggest that tissue-specific translational regulation is a means for differentially regulating expression of FGF-2 nuclear and cytoplasmic protein isoforms.…”
Section: Tgfgf214 Transgenic Micesupporting
confidence: 76%
See 2 more Smart Citations
“…We have identified bone as the principle target tissue for the physiological effects of FGF-2 overexpression during growth and development. This phenotype is consistent with in vitro data showing changes in the growth and differentiation of chondrocytes by addition of exogenous FGF-2 (Trippel et al, 1993) and human syndromes where mutation of FGFR tyrosine kinases primarily affect the skeletal system (Jabs et al, 1994;Muenke et al, 1994;Reardon et al, 1994;Rousseau et al, 1994;Shiang et al, 1994;Tavormina et al, 1995). The Western blots and RNase protection assays suggest that tissue-specific translational regulation is a means for differentially regulating expression of FGF-2 nuclear and cytoplasmic protein isoforms.…”
Section: Tgfgf214 Transgenic Micesupporting
confidence: 76%
“…The chondrodysplasia resulting from overexpression of the FGF-2 ligand is interesting in relation to skeletal malformations in human syndromes associated with mutations in the FGFRs. Mutation of FGFR1 causes Pfeiffer syndrome (Muenke et al, 1994), mutation of FGFR-2 causes Jackson-Weiss and Crouzon syndromes (Jabs et al, 1994;Reardon et al, 1994), and mutation of FGFR-3 causes achondroplasia (Rousseau et al, 1994;Shiang et al, 1994) (Olwin et al, 1994). There are several possible explanations for this discrepancy.…”
Section: Tgfgf214 Transgenic Micementioning
confidence: 84%
See 1 more Smart Citation
“…Crouzon syndrome is the most distinctive and common disorder of the autosomaldominant form of the craniofacial complex, and is characterized by the triad of premature craniosynostosis, orbital proptosis, and midfacial hypoplasia (1). Molecular analysis has identified mutations in the gene coding for fibroblast growth factor receptor 2 (FGFR2) on chromosome 10q25-26 (3). Recent studies have demonstrated that mutations in three of the four known FGFR genes are responsible for a variety of craniosynostosis syndromes, including Crouzon (4-6), Apert (7,8), Pfeiffer (9,10), and Jackson-Weiss (3,9,11) syndromes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that mutations in three of the four known FGFR genes are responsible for a variety of craniosynostosis syndromes, including Crouzon (4-6), Apert (7,8), Pfeiffer (9,10), and Jackson-Weiss (3,9,11) syndromes. Crouzon syndrome shows a broader spectrum of mutations in the FGFR2 gene, and occasionally patients with Crouzon syndrome share identical mutations (Cys278Phe, Cys342Arg, and Cys342Tyr) with patients with Pfeiffer and Jackson-Weiss syndromes, respectively (3,8,10,11). The majority of mutations in FGFR2 are missense substitutions clustered around the third extracellular immunoglobulin-like domain, encoded by exons IIIa and IIIc.…”
Section: Introductionmentioning
confidence: 99%